(untitled) (Journal of Pharma Insights and Research, 2024)
The skin serves as a formidable barrier to drug penetration, primarily due to the stratum corneum. For successful transdermal drug delivery, the drug must overcome this barrier and reach the target site in sufficient concentrations. Drug molecules can penetrate the skin via the transcellular, intercellular, and appendageal pathways. The extent of drug permeation is influenced by factors such as the physicochemical properties of the drug, the nature of the vehicle, and the condition of the skin. Gels, being hydrophilic, can enhance drug permeation by increasing the hydration of the stratum corneum. Permeation enhancers, which reversibly alter the structure of the stratum corneum, can also improve drug permeation. Recent advancements in topical gel drug delivery include the use of nanotechnology, stimuli-responsive gels, combination therapy, natural polymers, and biodegradable materials. The delivery of biomolecules through the skin remains a challenge, and strategies such as iontophoresis, microneedles, and nanocarriers are being investigated. 3D printing technology enables the personalized fabrication of gels with precise drug dosing and customized release profiles. Despite significant advancements, challenges such as limited drug permeability, potential for skin irritation, and the need for long-term stability studies persist. Future research should focus on developing innovative strategies to overcome these challenges and optimize the performance of topical gels, involving the exploration of new drug-polymer combinations, advanced drug delivery technologies, and in silico modeling tools